2015
DOI: 10.2458/azu_rc.57.18198
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary Vegetational Changes in a Marsh Forest in Southeastern Brazil with Comments on Prehistoric Human Occupation

Abstract: This article presents a palynological study carried out on a sediment core from a peat deposit in Serra de Botucatu, in SÃo Paulo State, southeastern Brazilian Plateau. This region has been covered by grassland vegetation and forest patches throughout the recorded period. AMS radiocarbon dating plus palynological analysis of 27 samples from the sediment core allowed the recognition of several environmental changes that took place during the last 33,000 yr recorded in the core. The relationship between sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
8

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
3
0
8
Order By: Relevance
“…Além do impacto direto nos sistemas fluviais subtropicais brasileiros, as oscilações climáticas do Quaternário Tardio induziram significativas mudanças na paleovegetação desta região. Estudos palinológicos revelaram importantes eventos de regressão e expansão das florestas e dos cerrados/cerradões do Estado de São Paulo ao longo dos últimos 116 mil anos (Ledru et al, 2005, Ledru et al, 2009Bissa & Toledo, 2015;Aviles et al, 2019;Garcia et al, 2004). Mudança na cobertura vegetal dominante é um fator de contorno que afeta diretamente a dinâmica fluvial das bacias hidrográficas ao longo do tempo (Bull, 1991;Vandenberghe, 2003).…”
Section: áRea De Estudounclassified
See 3 more Smart Citations
“…Além do impacto direto nos sistemas fluviais subtropicais brasileiros, as oscilações climáticas do Quaternário Tardio induziram significativas mudanças na paleovegetação desta região. Estudos palinológicos revelaram importantes eventos de regressão e expansão das florestas e dos cerrados/cerradões do Estado de São Paulo ao longo dos últimos 116 mil anos (Ledru et al, 2005, Ledru et al, 2009Bissa & Toledo, 2015;Aviles et al, 2019;Garcia et al, 2004). Mudança na cobertura vegetal dominante é um fator de contorno que afeta diretamente a dinâmica fluvial das bacias hidrográficas ao longo do tempo (Bull, 1991;Vandenberghe, 2003).…”
Section: áRea De Estudounclassified
“…Dados isotópicos de espeleotemas da caverna de Santana (Cruz et al, 2006) e de palinologia da Cratera de Colônia, São Paulo (Ledru et al, 2005;, de Curucutu, na Serra do Mar (Pessenda et al, 2009), de Jaguariúna, Botucatu e Pirassununga (Scheel-Ybert et al, 2003), da Estação Ecológica de Jataí (EEJ), em Luiz Antônio, SP (Souza et al, 2013;Celarino et al, 2013), de Bofete (Bissa & Toledo, 2015) e de Campinas (Aviles et al, 2019), possibilitam inferir mudanças paleoambientais ocorridas no sudeste brasileiro, sobretudo no Estado de São Paulo, desde o Pleistoceno Tardio até o presente.…”
Section: Paleoclima No Sudeste Brasileiro Durante O Quaternário Tardiounclassified
See 2 more Smart Citations
“…According to the paleoenvironmental records of Serra da Mantiqueira and Núcleo Curucutu in Serra do Mar (Pessenda et al 2009), the climate conditions were cold and humid in Southeastern Brazil near the end of the Last Glacial Maximum (LGM). The records apply for Jacareí in Paraiba do Sul River Valley (Garcia 1994, Garcia et al 2004 and São Paulo plateau (Bissa and Toledo 2015). From the Pleistocene end to the Holocene beginning, all of studies developed in the Paulista plateau (De Oliveira et al 2014) showed evidence of temperature increase from 18,000 cal yr BP, with the stabilization of climatic conditions in the last 8,000 cal yr BP.…”
Section: Introductionmentioning
confidence: 97%